Система количественного учета жидких продуктов в герметичных резервуарах; Контроль. Диагностика; № 13 - Сорокин П. В. Павел Владимирович; Солдатов А. И. Алексей Иванович; Солдатов Д. А. Дмитрий Алексеевич; Хаскова Е. С. Екатерина Сергеевна; Квасников К. Г. Константин Григорьевич; Буй Ван Донг (2014, 2014)
Заглавие с экрана